Pendampingan Penyusunan Laporan Keuangan Masjid Istiqomah Perum Griya Wonorejo Karanganyar - Arif Lukman Santoso; Falikhatun Falikhatun; Susanto Tirtoprojo; Hasim Hasim (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service project aimed to enhance the financial accountability and transparency of Masjid Istiqomah by implementing proper financial reporting standards. The specific objectives were to: 1) Identify and inventory the mosque's assets and financial transactions, 2) Provide training and mentoring on applying Indonesian financial accounting standards for non-profit organizations (ISAK 35) and sharia-compliant philanthropy (PSAK 409), and 3) Assist the mosque's treasurer in preparing a complete set of financial statements for accountability to the congregation. The project employed the Participatory Rural Appraisal (PRA) method, focusing on collaborative mentorship. The execution was conducted in phases: a Focus Group Discussion (FGD) for initial assessment, an asset identification and data collection phase, a series of technical workshops and intensive mentoring sessions on preparing financial statements, and a finalization phase. The activities were carried out by a team of lecturers and students from UNS, working directly with the mosque's treasury officials. The project successfully produced Masjid Istiqomah's first complete set of financial statements for the period January 1 - June 30, 2025. The outputs include: a Statement of Financial Position, a Statement of Activities, a Statement of Changes in Net Assets, and Notes to the Financial Statements. Furthermore, the competence of the mosque's treasurer in understanding and practicing sharia-based financial recording and reporting was significantly improved. A simple Standard Operating Procedure (SOP) for ongoing bookkeeping was also established. This project provides significant practical value by transforming the mosque's financial management from simple cash notes to a standardized, transparent, and accountable system. It strengthens the mosque's social trust (legitimacy) by enabling clear financial accountability to its stakeholders (the congregation). The project also serves as a practical model for other mosques and non-profit organizations seeking to implement ISAK 335 and PSAK 409, demonstrating how academic knowledge can be directly applied to solve real-world community problems. The novelty of this work lies in its focused, hands-on application of complex sharia accounting standards (PSAK 409 and ISAK 335) within the specific, often overlooked context of a local mosque. While these standards exist theoretically, their practical implementation at the grassroots level is limited. This project bridges that gap by translating accounting theory into a simple, manageable framework for non-accountant mosque officials, ensuring both religious compliance (sharia principles) and financial accountability. The participatory mentorship model ensures the solution is sustainable and owned by the community.